Bolstering spatial learning in the primary classroom: identifying the factors underlying primary teachers’ spatial pedagogical practices - Rocha, Kelsey; Lussier, Catherine M.; Atit, Kinnari (Frontiers in Education, 2025)
Teachers’ cognition and affect can influence their pedagogical choices, which in turn can shape the development of their students’ spatial skills. Here we examined the relations between primary teachers’ spatial cognition, affect, and their inclination for choosing teaching practices, such as models and diagrams, that engage and facilitate spatial learning. Seventy-seven K-6 teachers completed measures of spatial skills, spatial anxiety, spatial habits of mind, and a measure of preferences for spatial pedagogy. Additionally, we assessed and controlled for their general reasoning and general anxiety. Results revealed primary teachers’ spatial skills were positively associated with their spatial habits of mind and their preference for using spatial strategies for teaching science content. Yet, their pedagogical preferences for teaching math content varied with their teaching experience. Teachers’ spatial skills and spatial anxiety were not related. These findings have implications for how to leverage teacher education programs to bolster primary STEM learning and outcomes.